A cohort-based assessment of drug use trends during the COVID-19 pandemic: relationship with mood and sociodemographic factors in Brazil - Heidrich, Nubia; Nin, Maurício Schüler; Almeida, Felipe Borges; Constant, Hilda M. R. M.; Freese, Luana; Barros, Helena M. T. (Frontiers in Psychiatry, 2025)
The COVID-19 pandemic has brought significant challenges, including severe psychological consequences, especially for vulnerable individuals, such as those with substance use disorders. This study investigated the impact of the pandemic on substance use patterns and psychological health in Brazilians, exploring associations with sociodemographic factors to identify groups at higher risk. Data were collected online to assess self-reported substance use through the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST), and psychological state, using the Depression, Anxiety and Stress Scale (DASS-21) and level of social distancing. The research was conducted in three waves: September-October 2020, April-May 2021, and September-November 2022. The ASSIST (alcohol, cannabis, hallucinogens, and cocaine/crack) and DASS-21 (anxiety, depression, and stress) scores decreased over time. Regarding sociodemographic data, being male, single, with less education, lower income and lower social distancing showed associations with alcohol and cannabis scores. All drug scores showed associations with psychological symptoms and time, suggesting a possible adaptation or resilience of the sample to the challenges of the pandemic. These findings highlight the importance of monitoring patterns of substance use and mental health in times of crisis, especially in vulnerable populations. Such knowledge is essential to inform public health strategies and prepare health systems to face future global crises.